The relationship between weight stigma, weight bias internalization, and physical health in military personnel with or at high-risk of overweight/obesity. (March 2019) - Shank, Lisa M.; Schvey, Natasha A.; Ekundayo, Kendra; Schreiber-Gregory, Deanna; Bates, Dawn; Maurer, Douglas; Spieker, Elena; Stephens, Mark; Tanofsky-Kraff, Marian; Sbrocco, Tracy
Highlights: Military-specific weight stigma was related to reporting a medical condition. General weight stigma was not related to reporting a medical condition. Weight bias internalization was not related to reporting a medical condition. Abstract: Perceived weight stigma is associated with adverse health indices, such as elevated cortisol, lipid/glucose dysregulation, and poorer self-rated health. This relationship may be particularly relevant for military personnel, given the cultural emphasis on fitness and weight/shape. Therefore, we investigated the relationship between weight stigma and physical health in 117 active duty personnel (66.7% male; 56.4% non-Hispanic White; age: 30.8 ± 7.4 years; BMI: 29.5 ± 2.5 kg/m 2 ). Participants reported weight stigma (general and military-specific), weight bias internalization, and the presence (≥1; n = 55) or absence ( n = 62) of medical conditions. Logistic regressions were conducted examining the ability of weight stigma (general or military-specific) and weight bias internalization to predict the presence or absence of medical conditions. General weight stigma was not significantly associated with the presence of a medical condition ( p > .05). However, individuals with military-specific weight stigma scores twice that of their peers were over three times more likely ( p = .04) to report a medical condition. Weight bias internalization was not significant in any model ( p s > .20). Longitudinal studies should prospectively examine the relationship between weight stigma in the military setting and health among service members.